Peran Fintech Syariah dalam Mendorong Pertumbuhan Ekonomi Umat di Era Digitalisasi Keuangan - Nurazizah, Tia; Vidiati, Cory (SENTRI: Jurnal Riset Ilmiah, 2025)
The advancement of digital technology has brought substantial transformation to the global financial landscape, including in Indonesia, through the emergence of financial technology (fintech) as a modern financial innovation. In this context, Islamic fintech represents a distinctive development that integrates digital innovation with Islamic economic principles, positioning it as a strategic driver for the economic empowerment of Muslim communities. This study aims to analyze how Islamic fintech concretely contributes to the economic growth of the ummah, particularly through inclusive access to sharia-compliant financial services in the era of financial digitalization. Using a qualitative descriptive approach based on literature studies from OJK, Bank Indonesia, DSN-MUI, and several Islamic fintech case studies in Indonesia, the research identifies that Islamic fintech plays a significant role in expanding financing opportunities for MSMEs, fostering productive investment aligned with Islamic ethics, and strengthening financial inclusion in underserved regions. The findings reveal that Islamic fintech contributes to the real sector by channeling funds into halal business activities, supporting entrepreneurial development, and enhancing social welfare through digital zakat, infaq, and waqf platforms. However, the study also highlights challenges, including limited adaptive regulation, low financial and digital literacy, and the need for stronger infrastructure and data security systems. These results imply that optimizing Islamic fintech’s potential requires synergy among the government, financial institutions, academia, and society to create a sustainable, equitable, and inclusive Islamic financial ecosystem capable of accelerating the economic growth of the Muslim community in the digital era.